2020
DOI: 10.17305/bjbms.2020.5236
|View full text |Cite
|
Sign up to set email alerts
|

Can NLR, PLR and LMR be used as prognostic indicators in patients with pulmonary embolism? A commentary

Abstract: We read with great interest the article “Prognostic role of NLR, PLR, and LMR in patients with pulmonary embolism” by Köse et al.[1]. They found that the neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and lymphocyte-monocyte ratio (LMR) were related to the prognosis and clinical severity of patients with pulmonary embolism (PE). First of all, we congratulate the authors for their invaluable contribution to literature. However, we think that there are some points that should be discussed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Since it is a lifethreatening disease, early detection of thrombus that may occur in the main branches with non-invasive easily accessible markers will accelerate the diagnosis and treatment processes (11). Studies have shown the relationship between inflammatory markers such as d-dimer and NLR and thrombus localization (4,12). However, the relationship between SIRI or SII and thrombus in patients with PE has not been demonstrated in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it is a lifethreatening disease, early detection of thrombus that may occur in the main branches with non-invasive easily accessible markers will accelerate the diagnosis and treatment processes (11). Studies have shown the relationship between inflammatory markers such as d-dimer and NLR and thrombus localization (4,12). However, the relationship between SIRI or SII and thrombus in patients with PE has not been demonstrated in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these markers are d-dimer, neutrophil-lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR), and lymphocyte monocyte ratio (LMR). However, the superiority of these markers over each other has not been documented (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, macrolide antibiotics were also prescribed to COVID-19 patients and their anti-inflammatory and immunomodulatory effects are well documented and could interfere with the interpretation of the results [23,24]. A commentary by Bedel et al also highlights the importance of the relative timing between blood sampling and disease onset, especially considering the potential impact that the various drugs taken during this time period can have on NLR, PLR and LMR values [25]. Regardless of its limitations, it was recommended that SARS-CoV-2-positive patients with NLR >6.11 should be started on corticosteroid therapy, which reflects the amount of importance given to this biomarker during the pandemic [26].…”
Section: Introductionmentioning
confidence: 99%